Tourette Syndrome and Klippel-Feil Anomaly in a Child with Chromosome 22q11 Duplication - Raymond A. Clarke; Zhi Ming Fang; Ashish D. Diwan; Donald L. Gilbert (Case Reports in Medicine)
This is the first case description of the association of Klippel-Feil Syndrome (KFS), Tourette Syndrome (TS), Motor Stereotypies, and Obsessive Compulsive Behavior, with chromosome 22q11.2 Duplication Syndrome (22q11DupS). Neuropsychiatric symptoms in persons with 22q11.2 deletion, including obsessive compulsiveness, anxiety, hyperactivity, and one prior case report of TS, have been attributed to low copy number effects on Catechol-O-Methyltransferase (COMT). However, the present unique case of 22q11DupS and TS suggests a more complex relationship involving another gene(s) at or near this locus.